Community Recovery Following the Deepwater Horizon Oil Spill: Toward a Theory of Cultural Resilience. Issue 2 (1st February 2017) - Clarke, Hannah E.; Mayer, Brian
ABSTRACT: Culture plays an important role in communities' abilities to adapt to environmental change and crises. The emerging field of resilience thinking has made several efforts to better integrate social and cultural factors into the systems-level approach to understanding social–ecological resilience. However, attempts to integrate culture into structural models often fail to account for the agentic processes that influence recovery at the individual and community levels, overshadowing the potential for agency and variation in community response. Using empirical data on the 2010 BP oil spill's impact on a small, natural-resource-dependent community, we propose an alternative approach emphasizing culture's ability to operate as a resource that contributes to social, or community, resilience. We refer to this more explicit articulation of culture's role in resilience as cultural resilience . Our findings reveal that not all cultural resources that define resilience in reference to certain disasters provided successful mitigation, adaptation, or recovery from the BP spill.